2003
DOI: 10.1103/physrevlett.90.106101
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous N Incorporation onto a Si(100) Surface

Abstract: Initial nitridation of the Si(100) surface is investigated using photoemission, ion-scattering and ab initio calculations. After dissociation of NO or NH3, nitrogen atoms are found to spontaneously form a stable, highly coordinated N[triple bond]Si(3) species even at room temperature. The majority of the N species is incorporated into the subsurface Si layers occupying an interstitial site, whose atomic structure and unique bonding mechanism is clarified through ab initio calculations. This unusual adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…N1 and N2 peaks may straightforwardly be assigned as due to the N atoms without any N-H bond (Si 3 BN) and those with one N-H bond (Si 2 @NH), respectively, in comparison to N3 for Si-NH 2 . In fact, the previous experiments agree well on the binding energy of the fully dissociated N species for NO or NH 3 adsorption on Si(1 0 0) as being identical to that of N1 [21,23]. A similar N 1s binding energy is also reported for the Si 3 BN species at the Si-rich interface of SiON/Si(001) [24].…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…N1 and N2 peaks may straightforwardly be assigned as due to the N atoms without any N-H bond (Si 3 BN) and those with one N-H bond (Si 2 @NH), respectively, in comparison to N3 for Si-NH 2 . In fact, the previous experiments agree well on the binding energy of the fully dissociated N species for NO or NH 3 adsorption on Si(1 0 0) as being identical to that of N1 [21,23]. A similar N 1s binding energy is also reported for the Si 3 BN species at the Si-rich interface of SiON/Si(001) [24].…”
Section: Resultssupporting
confidence: 77%
“…Although such a subsurface incorporation successfully explain the depth distribution observed here, a minor occupation of the shallower sites S or I cannot be excluded. In addition, one should be careful in a direct comparison of the earlier theoretical results suggesting the I or S [6,25] with our recent one [21] because the previous ones assumed all surface Si dangling bonds are saturated by H atoms in contrast to our assumption of no H adsorbates [21]. Based on this difference, it may be argued that the ''deep'' subsurface incorporation occurs only at a temperature high enough to desorb H atoms.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…(It is worth noting that in a recent study of room-temperature silicon nitridation by NO and NH 3 , Kim et al have reported that nitrogen accumulates in a subsurface region. 40 ) On freshly prepared grafted surfaces the oxygen amount was found to be of the order of two monolayers. The O 1s/C 1s and Si 2p/O 1s intensity ratios, both increasing with Â, show that such an oxygen is localized at the interface between the silicon surface and the carbonaceous layer.…”
Section: The Influence Of Oxygenmentioning
confidence: 97%